2014
DOI: 10.1016/j.ejvs.2014.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of Calcifying Nanoparticle in the Development of Hyperplasia and Vascular Calcification in an Animal Model

Abstract: This research confirms the ability of systemic inoculation of human-derived NPs to accelerate hyperplasia and stimulate calcification in localized areas of arteries previously submitted to endothelial damage, while it was harmless in healthy arteries. Atorvastatin was demonstrated to slow down this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…Local intravascular gene delivery is an effective strategy for preventing restenosis during angioplasty procedure [45, 46]. Since previous study reported that endogenous Smad3 expression reached a maximal level around 14 days after vascular injury [16], we selected this time point for evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Local intravascular gene delivery is an effective strategy for preventing restenosis during angioplasty procedure [45, 46]. Since previous study reported that endogenous Smad3 expression reached a maximal level around 14 days after vascular injury [16], we selected this time point for evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Jeziorska et al observed that the arterial calcification microenvironment has a histochemical resemblance to areas of osteogenesis and bone remodeling (eg, the foci of osteoid matrix, osteocytes, and thin bone trabeculae) 96. Modern histopathologic research further confirmed this hypothesis and demonstrated that cells in areas of vascular calcification are derived from osteoclastic and osteoblastic cells 97, 98…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…64 Such preatherosclerotic niches are characterized by endothelial activation and the osteochondrogenic dedifferentiation of VSMCs, which produce abundant extracellular matrix, 64 resembling that in human atherosclerotic plaque development. 93,196 Combining CPP administration with balloon-induced vascular injury provokes development of intimal hyperplasia in 50% to 90% of animals, 32,142,143 which vary in the presence of calcium phosphate deposits, 32,64,142,143 suggesting a secondary hit (eg, dyslipidemia or a chronic low-grade inflammation) as prerequisite for vascular calcification. Intravenous CPP administration has to date only been performed in normolipidemic animals, and it remains unclear whether CPPs are involved in the transition of developing plaques to calcified plaques.…”
Section: Dynamics Of Cpps In Vivomentioning
confidence: 99%
“…In humans, elevated levels of CPPs have been primarily associated with increased vascular calcification, 3,9,149 whereas in rodents CPP administration is associated with intimal hyperplasia and atherosclerosis 64 and a highly variable frequency of vessel calcification. 32,64,142,143 It should, however, be noted that the animal models currently used for CPP administration are normolipidemic, without a renal phenotype. Performing further studies to investigate the ability of CPPs to induce or aggravate vascular calcification would best be conducted in animal models that are predisposed to vascular calcification, such as partially nephrectomized rodents, or animals with dyslipidemia or inherently disturbed mineral homeostasis.…”
Section: Cpps In Cardiovascular Pathophysiologymentioning
confidence: 99%